2017
DOI: 10.1161/jaha.117.005613
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Arterial Stiffness in Kenyan Adolescents With α + Thalassemia

Abstract: BackgroundRecent studies have discovered that α‐globin is expressed in blood vessel walls where it plays a role in regulating vascular tone. We tested the hypothesis that blood pressure (BP) might differ between normal individuals and those with α+thalassemia, in whom the production of α‐globin is reduced.Methods and ResultsThe study was conducted in Nairobi, Kenya, among 938 adolescents aged 11 to 17 years. Twenty‐four‐hour ambulatory BP monitoring and arterial stiffness measurements were performed using an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
1
8
1
Order By: Relevance
“…The detection of α-globin and AHSP in mouse and human ECs suggests that the roles of these proteins in blood vessels are conserved across species (Figure 1). However, Etyang et al reported normal blood pressure in a cohort of Kenyan adolescents with α-thalassemia trait caused by the loss of 2 α-globin genes (51). This contrasts with our finding that the systemic blood pressure of Hba1 −/− mice (which also lack 2 α-globin genes) was lower than that of control animals.…”
Section: Table 1 Pe Dose Responses For Vasoconstriction Of Isolated contrasting
confidence: 99%
“…The detection of α-globin and AHSP in mouse and human ECs suggests that the roles of these proteins in blood vessels are conserved across species (Figure 1). However, Etyang et al reported normal blood pressure in a cohort of Kenyan adolescents with α-thalassemia trait caused by the loss of 2 α-globin genes (51). This contrasts with our finding that the systemic blood pressure of Hba1 −/− mice (which also lack 2 α-globin genes) was lower than that of control animals.…”
Section: Table 1 Pe Dose Responses For Vasoconstriction Of Isolated contrasting
confidence: 99%
“…A related study of Kenyan adolescents found no association between the 3.7 kb gene deletion and 24-hour ambulatory blood pressure. 16 Our study extends that observation into a population of older Black American adults with a range of social, economic, and medical risk factors where we find no association between HBA copy number and the clinical outcome of hypertension. One relevant co-morbidity is chronic kidney disease, which was recently found to be associated with HBA copy number in a separate study also performed in the REGARDS cohort.…”
Section: Discussionsupporting
confidence: 79%
“…11 The most common alpha globin gene deletion (−3.7 kb) was recently found to be associated with enhanced vasodilation in people of African and Asian ancestry; 12,13 however, the same deletion was not associated with ambulatory blood pressure in a study of healthy Kenyan adolescents. 14 The question of whether this alpha globin gene insertion/deletion is associated with hypertension risk or blood pressure among older adults with multiple medical comorbidities remains unaddressed. To fill this knowledge gap, we used digital droplet PCR to determine HBA copy number in 10,000 Black participants from the national, longitudinal REGARDS (Reasons for Geographic and Racial Differences in Stroke) study cohort.…”
Section: Introductionmentioning
confidence: 99%
“… 25 Using 24-hour ambulatory arterial blood-pressure monitoring, Etyang et al showed normal arterial blood pressure in Kenyan adolescents with α-thalassemia. 26 Therefore, it can be postulated that changes in arterial blood pressure in α-thalassemic carriers might be the result of the interaction between the two previously mentioned mechanisms, ie, the effect of deficiency in the α subunit in the endothelium and the increase in HbH. The current finding of low VO 2max and relatively high resting systolic blood pressure in 3.7 α rightward deletion is a very important one, and should raise the alert toward possible increased cardiovascular risk in this carrier group.…”
Section: Discussionmentioning
confidence: 99%